Islamic moral judgment on transparency and confidentiality and its nursing applications: expository analysis - Mohamad Ismail, Mohamad Firdaus; Hashi, Abdurezak Abdulahi; Nurumal, Mohd. Said; Md Isa, Muhammad Lokman (MEDWIN Publishers, 2017)
Health workers like nurses have the responsibility to provide health services to patients. By doing so, nurses are expected to contribute to the preservation of health, and thus save the lives of their patients. At the same time, nurses are tasked to ensure the delivering of information to the patient accurately and their privacy stuff is well kept confidential. Indeed, this duty is a part of the core values in nursing to “respect for human rights, including cultural rights, the right to life and choice, to dignity and to be treated with respect, “however, as lifestyle is rapidly changing, there are instances in which health workers have to deal with cases which involve breaching of transparency and confidentiality like telling lies and disclose the private information, respectively. The doubt is if the task of the nurses is to tell the whole truth and maintaining confidentiality, what occurs when health service involves decisions which need to tell lies, or disclose private information such as discloses a patient’s history to the police to investigate further for the sake of society? Scholars in the field mention that, grounded along the utilitarian perspective, for instance, the healthcare provider will do everything which will lead the good consequences to maximize happiness and welfare, including telling lies and disclose a private information. Nevertheless, what about the cases in which activities are sought to serve a greater purpose or prevent harm of individual or society? Can a nurse refuse to tell a lie and disclose private information due to respect for patient’s autonomy? This paper uses analytical and comparative methods to address ethical issues of transparency and confidentiality from Islamic and conventional perspectives. Nursing implication: Islamic view on this issue give a clear cut the condition for Muslim nurses to proceed or decline in maintaining the transparency and confidentiality of information. The subject area to investigate the degree of knowledge among nurses regarding the Islamic moral judgement on this event is extremely recommended for future management.